Illicit Activities and Border Control in Ngoma, Namibia - Simataa, Charlene; Shaamhula, Loide; Johannes, Geldenhuys (Scientia Militaria - South African Journal of Military Studies, 2024)
Ensuring border security and control is essential for maintaining national peace and stability, as it involves security forces monitoring border areas to safeguard communities. The Ngoma border faces difficulties, sharing boundaries with Zambia and Botswana. The current study explored key illegal activities, their effects on the community, and the existing border control measures and challenges. Despite the established border control efforts, significant illicit activities persist in Ngoma. Using a purposive sampling approach, the research obtained data through individual interviews and focus groups discussions with members of the Namibian Police Force, the Namibian Defence Force, Customs and Immigration officials, and community residents. The data were analysed through thematic analysis, revealing that, despite existing control measures, activities, such as poaching, illegal fishing, smuggling, and unauthorised border crossings, remain prevalent. The findings further indicate that border control in the area appears ineffective, largely due to a shortage of adequately trained personnel, limited screening equipment, and a lack of essential resources, such as patrol vehicles and aerial surveillance systems. Based on these insights, border control at Ngoma can be enhanced by integrating modern technologies, such as biometric identification, automated license plate recognition, and drones to improve efficiency and security. Furthermore, implementing training and capacity-building programmes for border law enforcement and customs officers would be advantageous. Engaging local communities through community policing also strengthens relationships between law enforcement and residents. Additionally, regional collaboration with neighbouring countries could help reduce illicit border activities and build stronger diplomatic connections.